Non-fragile extended dissipativity-based state feedback control for 2-D Markov jump delayed systems - Dai, Mingcheng; Huang, Zhengguo; Xia, Jianwei; Meng, Bo; Wang, Jian; Shen, Hao (Applied mathematics and computation, 2019)
This work deals with the issue of extended dissipativity-based state feedback control for an array of two-dimensional Markov jump systems established upon Fornasini–Marchesini local state-space model, in which a kind of state delays is thoroughly taken into account. Meanwhile, the non-fragile control scheme is adopted to cope with the imprecisions occurring in the realization of the controller. The primary target is to devise a novel controller ensuring that the closed-loop system actualizes not merely the stochastic stability, but also meets a specified extended dissipative property. Through selecting a suitable Lyapunov–Krasovskii functional and applying a concise matrix decoupling approach, some criteria are derived to guarantee the solvability of the admissible controller. Ultimately, in order to validate the availability and practicability of the developed results, a simulation example is provided.